Microstructural characteristic of NiTi coating on stainless steel by plasma transferred arc process - Ozel, Serkan; Kurt, Bulent; Somunkiran, Ilyas; Orhan, Nuri (Elsevier Science Sa, 2008)
In this study, NiTi powder mixture was coated on the surface of an austenitic stainless steel (AISI 304) by plasma transferred arc (PTA). Coating was carried out by using 80, 90, 100 A current density under Ar atmosphere. Coating layer and interface were examined with SEM, EDX, XRD analysis and micro hardness test. Thickness of coating increased with current density. No cracks or pores were detected in the interface. Higher arc current densities caused a coating layer poor in NiTi alloy. Secondary phases such as Cr2Fe7Ni, Fe7Cr2Ni and Ni3Ti also formed in the coating layer. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: PTA; coating; NiTi